Automatic Power Factor Compensation (APFC) For Industrial Power Use to Minimize Penalty - Babar Omakr; Sonawane Akshay; Kaygude Akshay; Ghalame Suraj; Shende Yashvant (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In this proposed system, two zero crossing detectors are used to detect the zero-crossing of voltage and current. The project is designed to minimize fines for industrial units using automatic power factor regulators. The microcontroller used in this project belongs to the 8051 0. family the time delay between the 0-voltage pulse and the 0 current pulses is duly generated by the appropriate amplifier circuits operating in the comparator mode. The comparator is supplied to the two interrupt pins of the microcontroller. The program takes over to operate the appropriate number of relays from its output to introduce shunt capacitors into the load circuit to gain power factor until it is almost uniform. The capacitors and relays are interfaced with the microcontroller using a relay driver. It displays the time delay between current and voltage on the LCD. In addition, the design can be improved by using a thyristor control switch instead of a relay control to avoid the contact pitting common when switching torsion capacitors due to the high rush current.
Keywords: Active Power; Reactive Power; Power Factor; AT89C52 Microcontroller; Penalty; Capacitor Banks; Current Transformer; Voltage or Potential Transformer